The concubinate in Mexican Private International, law - Silva, Jorge Alberto (UNIVERSIDAD DE SONORA, 2017)
The lack of Mexican regulation related to the problems of international legal traffic agreed with the concubine, makes it necessary to set goals and establish clear rules that include their regulation. For that, it is necessary for our legislators to put themselves to work and to think about solutions.Although it is certainly necessary to take into account various human rights, already recognized in general terms, it will also be necessary to concretize the actual data or elements to be taken into account. It is also necessary to start by emphasizing the qualification of the situation, in the capacity to constitute the Union, the form (including the written and registered), the relations of couple (taking into account their customs, from the law of the habitual residence), as well as the effects of the termination of the concubine relationship. In the international conventional area, it is necessary to contribute to a convention on the subject, recognizing the rights, registries and effects.